Comparison of therapeutic effect of topical Nigella with Betamethasone and Eucerin in hand eczema. (1st December 2012) - Yousefi, M.; Barikbin, B.; Kamalinejad, M.; Abolhasani, E.; Ebadi, A.; Younespour, S.; Manouchehrian, M.; Hejazi, S.
Abstract Background Nigella sativa has been used in traditional medicine. Although it was investigated in different studies, its effect on hand eczema has not been studied yet. Objective To compare the effects of Nigella, Betamethasone and Eucerin on severity of hand eczema and patients' life quality. Methods In this randomized, controlled, double‐blinded clinical trial, we allocated new cases of hand eczema with 18–60 years of age in three therapeutic groups (Nigella, Betamethasone and Eucerin) by using permuted blocks for randomization. Patients applied medications twice a day and followed in a 4‐week period. The primary outcome of the study was changes in severity and life quality, which were assessed at the beginning, 14th and 28th days of the study by Hand Eczema Severity index (HECSI) and Dermatology Life Quality Index (DLQI) respectively. Results Sixty patients recruited in the study with 20 patients allocated in each study arm. Eighteen, 19 and 15 patients in Eucerin, Nigella and Betamethasone groups, respectively, attended at least one of the therapy sessions. Nigella and Betamethasone showed significantly more rapid improvement in hand eczema compared with Eucerin (P = 0.003 and P = 0.012 respectively); Nigella and Betamethasone ointments caused significant decreases in DLQI scores compared with Eucerin (P < 0.0001 and P = 0.007 respectively). No significant difference was detected in mean DLQI and HECSI of the Nigella and Betamethasone groups over time (P = 0.38 and P = 0.99 respectively). Conclusion It seems that Nigella might have the same efficacy as Betamethasone in improvement of life quality and decreasing severity of hand eczema.